Вы находитесь на странице: 1из 2

(I)If (x1,y1) & (x2,y2) are the two solutions of x^2 - dy^2 = 1 Then, (x1x2+dy1y2, x1y2+x2y1) & (x1x2-dy1y2,

x1y2-x2y1) are also the solutions. Notice, that (x1,y1) & (x2,y2) could be the same.

(II)Let (x1,y1) be the solution of x^2 - Dy^2 = c & (x2,y2) be the solution of x ^2 - Dy^2 = 1 Then, (x1x2+dy1y2, x1y2+x2y1) & (x1x2-dy1y2, x1y2-x2y1) are also the solutions o f x^2 - Dy^2 = c

(III) Let (x1,y1) be a solution of x^2 - Dy^2 = 1, Then the general solution of x^2 - Dy^2 = 1 is given by x = [(x1 + y1*sqrtD)^n + (x1 - y1*sqrtD)^n]/2 y = [(x1 + y1*sqrtD)^n + (x1 - y1*sqrtD)^n]/[2*sqrtD]

(IV) To solve 23x^2 + 1 = y^2, we see that a=1, b=5 satisfy 23x^2 + 2(=k) = y^2, hence x1 = 2ab/k = 5 & y1 = (b^2 + D*(a^2))/k = 24 are the solutions of 23x^2 + 1 = y^2 Again applying the composition, we get x = 2*x1*y1 = 2*5*24 = 240, y = D(x1)^2 + (y1)^2 = 23*(5^2) + (24)^2 = 1151 To solve 83x^2 + 1 = y^2, we see that a=1, b=9 satisfy 83x^2 - 2(=k) = y^2, henc e x1 = 2ab/k = 9 & y1 = (b^2 + D*(a^2))/k = 82 are the solutions of 83x^2 + 1 = y^2 Again applying the composition, we get x = 2*x1*y1 = 2*9*82 = 1476, y = D(x1)^2 + (y1)^2 = 83*(9^2) + (82)^2 = 13447

(V) To solve 61x^2 + 1 = y^2, we see that a=1, b=8 satisfy 61x^2 + 3(=k) = y^2, so choose m so that am+b is divisible by k & also m^2 - n should be as small as possible in absolute value, hence choose m so that m+8 is divisible by 3 and m^2 - 61 should be as small as possible in abs olute value => m = 7, so x1 = (am+b)/k = (1*7+8)/3 = 5 & y1 = (bm+na)/k = (8*7+61*1)/3 = 39 are the solutions of 61*(5^2) - 4 = 39^2

(VI) To solve 103x^2 + 1 = y^2, we see that a=1, b=10 satisfy 103x^2 - 3(=k) = y ^2, so choose m so that am+b is divisible by k & also m^2 - n should be as small as possible in absolute value, hence choose m so that m+10 is divisible by -3 and m^2 - 103 should be as small as possible in absolute value => m = 11, so x1 = (am+b)/k = (1*11+10)/3 = 7 & y1 = (bm+na)/k = (10*11+103*1)/3 = 71 are the solutions of 103*(7^2) - 6 = 71^2 Now, so choose m so that am+b is divisible by k & also m^2 - n should be as small as possible in absolute value, hence choose m so that 7m+71 is divisible by -6 and m^2 - 103 should be as small as possible in absolute value => m = 7, x1 = (am+b)/k = (7*7+71)/6 = 20 & y1 = (bm+na)/k = (71*7+103*7)/6 = 20 3 are the solutions => 103*(20^2) + 9 = (203)^2